(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article seeks to reflect on how Academic Research in the Arts has been dialoguing with artists who are developing practical work. More than that, as an artist who works in spaces like the street, thus having to maintain his popular knowledge, he also dialogues with the academy and its theoretical developments. Thus, the article seeks to raise reflections, relationships and possible questions about the exchange between academic research and practical development, and how these reflections can expand to other languages ​​and studies in the Performing Arts.